Lutra felina - James H. Honacki; Kenneth E. Kinman; James W. Koeppl (Alien Press, Inc. & The Association of Systematics Collections, 1982)
Lutra felina (Molina, 1782). Sagg. Stor. Nat. Chile, p. 284. TYPE LOCALITY: Chile. DISTRIBUTION: West coast of South America from N. Peru to Straits of Magellan. PROTECTED STATUS: CITES - Appendix I and U.S. ESA - Endangered. ISIS NUMBER: 5301412004023002001 as Lontra felina. Published as part of James H. Honacki, Kenneth E. Kinman & James W. Koeppl, 1982, Order Carnivora, pp. 244-289 in Mammal Species of the World (1 st Edition), Lawrence, Kansas, USA :Alien Press, Inc. & The Association of Systematics Collections on page 258, DOI: 10.5281/zenodo.7352980